Metode Bermain Peran dalam Meningkatkan Kemampuan Sosial Emosional Anak Usia 5 – 6 tahun di RA Al-Ittihad Krangkeng Indramayu - Faziyah, Muidatul; Muzfirah, Suci; Saomi, MuhamadRizka (Prodi PIAUD IAI Pangeran Dharma Kusuma Indramayu, 2025)
This research raises problems regarding how to improve the social emotional abilities of children aged 5-6 years which was carried out at RA Al-Ittihad, Krangkeng District, Indramayu Regency. This research aims to determine the increase in children's social emotional abilities with role playing activities at RA Al-Ittihad Indramayu. This research uses a type of Classroom Action Research (PTK) with a qualitative descriptive approach. Data collection was carried out using observation and performance techniques. The subjects in this study were 12 children aged 5-6 years who attended RA Al-Ittihad Indramayu. The data analysis technique in this research is a qualitative descriptive technique. The research results show that this role playing method can improve the social emotional abilities of children aged 5-6 years at RA Al-Ittihad Indramayu. This is proven by the results of research carried out in the second cycle. In the first cycle, the results showed that 9 students whose development (BSH) was not optimal and only 3 students who developed well. This result still did not reach the criteria for completeness and the second cycle was carried out again and there was an increase in developing according to expectations (BSH) of 5 children and developing very well (BSB) increasing to 10 children. It can be concluded that role playing can improve the social emotional skills of children aged 5-6 years at RA Al-Ittihad Indramayu and it can be seen that children are able to share, cooperate, tolerate and communicate well between peers.